People’s Participation in Waeng Nang Municipality Community Development Mueang Maha Sarakham District, Maha Sarakham Province: People’s Participation in Waeng Nang Municipality Community Development Mueang Maha Sarakham District, Maha Sarakham Province - Kalyanadhammo (Chantachit), Phra Phanomphon; Phrakhrusutaworathammakit; Phanthachai, Siamporn (RATANABUTH JOURNAL, 2024)
This research aimed to 1. Study the level of public participation in the development of Waeng Nang Subdistrict Municipality, Mueang District, Maha Sarakham Province, 2. Compare public participation in the development of Waeng Nang Subdistrict Municipality, Mueang District, Maha Sarakham Province classified by personal factors, and 3. Study the guidelines for developing public participation in the development of Waeng Nang Subdistrict Municipality, Mueang District, Maha Sarakham Province. Mixed-method research was conducted. The quantitative research used a questionnaire with a reliability value of 0.856 for the entire questionnaire. The sample consisted of 374 people aged 18 and over who were eligible to vote in Waeng Nang Subdistrict Municipality, Mueang District, Maha Sarakham Province. The data were analyzed by finding frequency, percentage, mean, and standard deviation, t-test, and F-test using the one-way analysis of variance. The qualitative research used in-depth interviews with 12 key informants and descriptive content analysis. From the study, the following results were found: 1. The participation of the people in the development of the Waeng Nang Subdistrict Municipality, Mueang District, Maha Sarakham Province, overall is at a high level ( = 3.48 S.D. = 0.42). When considering each aspect, it was found that it was at a high level in all aspects. 2. The results of the comparison of public participation in community development of Waeng Nang Subdistrict Municipality, Mueang District, Maha Sarakham Province, classified by gender, showed no difference overall. Therefore, the hypothesis was rejected. When considering each aspect, it was found that people of different genders had no difference in public participation in community development of Waeng Nang Subdistrict Municipality in all aspects. Therefore, the research hypothesis was rejected. And 3. The results of the analysis of the development guidelines for public participation in community development of Waeng Nang Subdistrict Municipality, Mueang District, Maha Sarakham Province found that local government administration by adjusting the perspective from “customer” to “citizen” who is aware of the rights, freedoms, and duties that people must perform towards society, which are important foundations of governance and public participation in local development.